PERANCANGAN KEBUN MINI HEMAT AIR DENGAN SISTEM MIKROIRIGASI FUZZY OTOMATIS MENGGUNAKAN ARDUINO - Rahmawati, Diana; Aji, Kunto (Universitas Trunojoyo Madura, 2015)
The system proposed in this research is mini garden which is a smart technology to provide plants and trees the required nourishment from the sunlight and to prevent the same from the harmful effects. System components used are humidity and temperature sensor, relay nodes for automatic control, and arduino manage using fuzzy system to control mini garden information. A model of mini garden is achieved. It was possible to do control plant growth through closely studying relationship between indoor environmental information and monitored information on crop itself. The mini garden fuzzy automatic control system will fully automate the management of a mini garden using the latest pervasive systems and technology. The proposed system controls and monitors humidity and temperature using a Arduino